Mixed ownership reforms and the transparency of nonstate‐owned enterprises: Evidence from China. (5th July 2022) - Zhao, Yueyang; Mao, Jinzhou
Abstract : This paper takes Chinese Shanghai and Shenzhen A‐share nonstate‐owned listed companies from 2008 to 2019 as samples to study the impact and mechanism of state‐owned capital participation on the transparency of nonstate‐owned enterprises. The results show that state‐owned capital participation has a significant positive impact on the transparency of nonstate‐owned enterprises. In terms of the mechanism of action, state‐owned capital participation positively impacts corporate transparency by increasing investors' attention. Further research finds that the positive effect of state‐owned capital participation on foreign‐funded enterprises and enterprises with few financing constraints is more prominent.